2021
DOI: 10.1136/bmjgh-2021-005659
|View full text |Cite
|
Sign up to set email alerts
|

The genomic epidemiology of multi-drug resistant invasive non-typhoidalSalmonellain selected sub-Saharan African countries

Abstract: BackgroundInvasive non-typhoidal Salmonella (iNTS) is one of the leading causes of bacteraemia in sub-Saharan Africa. We aimed to provide a better understanding of the genetic characteristics and transmission patterns associated with multi-drug resistant (MDR) iNTS serovars across the continent.MethodsA total of 166 iNTS isolates collected from a multi-centre surveillance in 10 African countries (2010–2014) and a fever study in Ghana (2007–2009) were genome sequenced to investigate the geographical distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 61 publications
(53 reference statements)
2
18
0
Order By: Relevance
“…Enteritidis in our study were multidrug resistant (resistant to ampicillin, SXT, nalidixic acid). This multidrug resistant clone has also been reported in bacteraemia in other parts of Africa [37,38]. We observed that S .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Enteritidis in our study were multidrug resistant (resistant to ampicillin, SXT, nalidixic acid). This multidrug resistant clone has also been reported in bacteraemia in other parts of Africa [37,38]. We observed that S .…”
Section: Discussionsupporting
confidence: 80%
“…Typhimurium ST313 and S . Enteritidis ST11 are dominant, human-adapted clones in sub-Saharan Africa (30) that are a major cause of invasive disease, with a corresponding high case-fatality rate (14). These serovars are justifiably vaccine development priorities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, resistance to third generation cephalosporins has been attributed to the presence of ESBL-encoding genes such as bla CTX-M, while non-susceptibility to fluoroquinolones has been associated with mutation of the gyr A gene. 104 Multidrug-resistant S . Typhimurium ST313 has now been reported from several countries in SSA, including Kenya, 105 Malawi, 67 Central African Republic, Senegal, Burkina Faso, 106 DRC, 107 Nigeria, 108 Ghana, 102 South Africa, and Mozambique, 79 , 109 where iNTS is endemic and produces septicemia in the absence of gastroenteritis.…”
Section: Resultsmentioning
confidence: 99%
“…In another study of the genetic characteristics and transmission patterns associated with multidrug-resistant iNTS serovars across SSA, 104 multiple multidrug-resistant iNTS serovar sequence types were identified as circulating in several countries that were sampled. High carriage rates observed in endemic sites in Kenya of MDR ST313 110 are likely to provide a reservoir for community spread of infection to vulnerable populations, adding new challenges in the control and prevention of iNTS disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation